Peran Pengatur Lalu Lintas Udara Dalam Memandu Lalu Lintas Penerbangan. Sebuah Kepemimpinan Otentik Tinjauan Literatur Sistematis - Panjaitan, Gery Arnetto Hasiholan; Supardam, Dhian (Politeknik Penerbangan Indonesia Curug, 2025)
This systematic literature review investigates the essential role of air traffic controllers (ATCs) in guiding air traffic and ensuring the safety and efficiency of aviation operations. The review synthesizes findings from various studies to elucidate the critical responsibilities of ATCs, such as maintaining situational awareness, managing airspace, and making prompt decisions in high-stress environments. Additionally, it explores the concept of authentic leadership within the air traffic control context, identifying how leadership qualities and practices influence operational success and team dynamics. Key traits of authentic leadership, including transparency, ethical behavior, and relational focus, are examined for their impact on communication, error reduction, and the cultivation of a safety-centric culture. The review emphasizes the importance of continuous professional development for ATCs to keep pace with technological advancements and increasingly complex airspace management demands. By integrating theoretical perspectives with practical insights, this review provides a comprehensive understanding of how authentic leadership can enhance the performance of air traffic control operations. The findings offer valuable recommendations for improving leadership practices and air traffic management systems, ultimately contributing to safer and more efficient aviation industry operations.